Immunization Finance Toolkit : A Resource for Policy-Makers and Program Managers - World Bank; GAVI Alliance (World Bank, Washington, DC, 2014)
Financing is a critical component of a sustainable Immunization program. The Immunization Financing Toolkit is a series of short briefs on different options for financing national immunization programs and vaccines. It is intended to serve as a resource for program managers and decision---makers in ministries of health, planning, and finance. The Toolkit brings together the most up---to---date knowledge on the characteristics of various types of= financing mechanisms as well as information on how the mechanisms are being implemented in practice, their potential benefits, and their limitations. Where possible, case studies on specific financing options are included. The field of immunization financing continues to evolve and the Toolkit will therefore be web---based and easily downloaded from the internet. As a web---based tool, the Toolkit contains links to other relevant websites for further understanding. The Toolkit is also available on a CD Rom. This version of the Toolkit is an update of the Immunization Financing Options produced by the Global Alliance for Vaccines and Immunization (GAVI Alliance) in 2001. Health sector funding and management have evolved over the last decade, making the previous document out---of---date. New and innovative financing mechanisms to support immunization and the health sector have been developed and the types and costs of vaccines have changed. In addition, policy---makers and development partners have become much more knowledgeable about health financing.